2013
DOI: 10.1111/bjh.12651
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and sexual function in long‐term survivors of haematological malignancy: using patient‐reported outcome measures to assess a neglected area of need in the late effects clinic

Abstract: SummaryProblems of sexual function and fertility in long-term survivors (≥5 years) of haematological malignancy are often neglected in clinic. Our centre carried out a questionnaire study in this population addressing patientperceived fertility and sexual function. 718 patients responded (56% of those invited; 39% Hodgkin, 45% non-Hodgkin lymphoma, 16% acute leukaemia). Respondent women were more likely to remain childless than a normal control population. Self-reported infertility was more likely in men than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 38 publications
1
63
1
1
Order By: Relevance
“…7 Previous studies have reported differences in sexual health and its predictive factors between male and female survivors, 3,[7][8][9] indicating that sexual outcomes need to be analyzed within sexes.…”
Section: 11mentioning
confidence: 99%
See 4 more Smart Citations
“…7 Previous studies have reported differences in sexual health and its predictive factors between male and female survivors, 3,[7][8][9] indicating that sexual outcomes need to be analyzed within sexes.…”
Section: 11mentioning
confidence: 99%
“…3,7,8 Those studies relied on questionnaires that focused on 1 or a few overarching questions. In 1 study that used a larger array of questions to compare sexual functioning in childhood cancer survivors with that in a group of healthy controls, more frequent low sexual interest, low sexual satisfaction, feeling sexually unattractive, orgasmic difficulty during intercourse, and a lower total number of sexual partners were reported among the survivors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations